2015
DOI: 10.1109/jstars.2014.2362511
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Validation of Waterline Extraction Approaches Using Single- and Dual-Polarimetric SAR Data

Abstract: In this study, the performance of two waterline extraction approaches is analyzed using dual-polarization Cosmo-SkyMed (CSK) Synthetic Aperture Radar (SAR) data and ancillary ground truth information. The single-polarization approach is based on multiscale normalized cuts segmentation; while, the dual-polarization one exploits the inherent peculiarities of the CSK PING PONG incoherent dual-polarimetric imaging mode together with a tailored scattering model to perform land/sea discrimination. The two approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…It must be pointed out that in this case, only a subset of polarimetric information is available, i.e., a single row of the scattering matrix is measured if compared to quad-polarimetric SAR imaging modes that measure the complete scattering matrix. Nevertheless, the latter costs in terms of limited swath width, reduced AOI (Angle Of Incidence) range and more demanding hardware constraints and, therefore, the dual-polarimetric SAR mode is here exploited that was shown to be effective in shoreline extraction [5,45,46].…”
Section: Sar Observationsmentioning
confidence: 99%
“…It must be pointed out that in this case, only a subset of polarimetric information is available, i.e., a single row of the scattering matrix is measured if compared to quad-polarimetric SAR imaging modes that measure the complete scattering matrix. Nevertheless, the latter costs in terms of limited swath width, reduced AOI (Angle Of Incidence) range and more demanding hardware constraints and, therefore, the dual-polarimetric SAR mode is here exploited that was shown to be effective in shoreline extraction [5,45,46].…”
Section: Sar Observationsmentioning
confidence: 99%
“…Concerning microwave data, due to their almost all-weather, day and night imaging capabilities, active synthetic aperture radar (SAR) sensors (e.g., Cosmo SkyMed-CSK, Terra SAR-X, Sentinel 1 constellations) are the most employed tool for water extraction and mapping of flooded areas (e.g., [20][21][22][23][24]), as well as for operational purposes (e.g., [25][26][27][28][29]). In SAR images, flooded areas can be easily detected because their backscattering signal intensity is significantly lower compared to other surface features (e.g., non-flooded areas) imaged by the sensors.…”
Section: Introductionmentioning
confidence: 99%
“…SAR-based sea oil slick observation is grounded on the fact that the presence of an oil layer over the sea surface reduces the short Bragg resonant waves and, therefore, generates a low backscatter area which appears, in conventional gray-tones SAR imagery, as a homogeneous patch darker than the background sea [5], [6]. Nowadays, there is wide consensus on the extra-benefits provided by polarimetric SAR data for a wide range of marine and maritime applications, including coastline extraction [7], [8], metallic target detection [9], [10] and sea oil slick monitoring [11]- [18]. In the framework of SAR-based sea oil slick observation it was shown that, once an electromagnetic model is available, polarimetric measurements can be successfully used to distinguish actual oil slicks from weak-damping look-alikes and to perform a rough zooning of the damping properties of the observed surfactant [11]- [13].…”
Section: Introductionmentioning
confidence: 99%